30 events that shaped the church : learning from scandal, intrigue, war, and revival - Gansky, Alton (Grand Rapids, Michigan : Baker Books, 2015)
Thirty course-altering events that shaped the history of the Christian church are brought to life by Alton Gansky.
Includes bibliographical references.
Keywords: Church history -- Miscellanea